1995
DOI: 10.1017/s0022215100131676
|View full text |Cite
|
Sign up to set email alerts
|

Is central hyperacusis a symptom of 5-hydroxytryptamine (5-HT) dysfunction?

Abstract: The subjective symptom of hyperacusis is described. The terms ‘hyperacusis’ and ‘phonophobia’ are considered to be synonymous as there is no recognized distinction between these two descriptions. Peripheral auditory pathologies with associated hearing sensitivity are reviewed and the likely mechanisms underlying the hyperacusis are listed. The neurological conditions, which have been reported to occur with hyperacusis, are reviewed. A separate aetiology of central hyperacusis is therefore proposed, with a symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
11

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 59 publications
2
60
0
11
Order By: Relevance
“…While the higher incidence of sensorineural hearing loss shown in the current study was more associated with nonmigrainous etiologies, noise exposure and age differences between the groups could also partly explain the difference. Given the association of migraine and phonophobia/hyperacusis [Marriage and Barnes, 1995], the migrainous groups may have a lower incidence of noise-induced sensorineural hearing loss, as they are more likely to avoid loud noise. Furthermore, the NMV group is more likely to have a higher incidence of sensorineural loss due to presbyacusis as this group was significantly older.…”
Section: Discussionmentioning
confidence: 99%
“…While the higher incidence of sensorineural hearing loss shown in the current study was more associated with nonmigrainous etiologies, noise exposure and age differences between the groups could also partly explain the difference. Given the association of migraine and phonophobia/hyperacusis [Marriage and Barnes, 1995], the migrainous groups may have a lower incidence of noise-induced sensorineural hearing loss, as they are more likely to avoid loud noise. Furthermore, the NMV group is more likely to have a higher incidence of sensorineural loss due to presbyacusis as this group was significantly older.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin regulates a variety of functions such as cognition, emotion, sleep, appetite, pain, circadian rhythms and endocrine activity [50] . Modifi cations of serotonin neurotransmission impair inhibitory associative learning [51] and have been proposed to contribute to tinnitus [52] and hyperacusis [53] .…”
Section: A Candidate Gene For Some Forms Of Tinnitus?mentioning
confidence: 99%
“…Patients reported that their sound tolerance was influenced by stress and tiredness, and that specific (though not necessarily loud) sounds caused physical pain and nerve grating [8]. Stephens [9] also reported a correlation between loudness tolerance and anxiety.…”
Section: Introductionmentioning
confidence: 99%